Analisis Metode Webqual 4.0 dan Importance Performance Analysis (IPA) pada Kualitas Website E-Health Surabaya - Mahida Hanifah Rahmadini; Iman Ali; Aldyan Fanindya; Dzarrin Alghiffari; Moch. Aburizal Fatwa (Universitas Mercu Buana Yogyakarta, 2022)
The existence of technology has provided many benefits for human life, one of which is in the field of patient registration both to puskesmas and hospitals. One of the patient registration websites that is widely used in Indonesian society is E-Health. E-Health is an online patient registration service that can be used to access patient registration at the Puskesmas and RSUD. To determine the quality of the website, it is necessary to measure. These measurements need to be carried out to determine the quality of a website so that we can understand the opinions of users of a website whether users are satisfied enough or the quality of the website still needs to be improved. The implementation of this research uses the webqual 4.0 method with three indicators, namely Usability (usability), Information Quality (quality of information), Service Interaction Quality (service interaction) and the Importance Performance Analysis (IPA) method as a calculation method. After measuring the results of this study, the E-Health website needs to improve its performance so that the level of performance (Performance) is higher than the level of expectation (Importance), especially on the Information Quality variable and Service Interaction Quality indicator no 8 which is located in quadrant A